Anabolic indices in junior athletes versus their fitness rates in post-training rehabilitation periods - Samikulin, P. N.; Gryaznykh, A. V.; Kuchin, R. V. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to rate the hormonal transformations and their correlations in junior athletes versus their physical activity and muscular loads in the rehabilitation periods. Testosterone and cortisol levels were tested versus the background values straight after and one hour after the exercise in the recovery process, with the anabolic indices being calculated. Strenuous physical loads were secured by 30/60min cycle ergometer practices rated by 2W/ kg of body mass, with the cadence of 60 revolutions per min. Subject to the study were 17-23 year-old athletes (n=52) grouped by the initial fitness and exercise rates. The study found a correlation of the metabolic index with the muscular load with background cortisol levels. Normally the index was found to fall after the cycle ergometer test and grow in case of fatigue and/or overtraining.